Study on the impact of macroeconomics factors toward non-performing loans in Malaysia / Muhammad Safiuddin Abu Samah and Nur Syafiqah Faharul Radzi - Abu Samah, Muhammad Safiuddin; Faharul Radzi, Nur Syafiqah (Faculty of Business and Management, 2016)
Project paper titled “Study on the Impact of Macroeconomics Factors toward Non-Performing Loans” is conducted as partial requirement to fulfill the requirement as needed by the faculty of Business Management, Universiti Teknologi Mara (UiTM). The intention of this study is to determine the relationship between independent variable; growth domestic products, inflation rate, interest rate and unemployment rate toward the dependent variable which non-performing loans. Data used in this research is secondary data such as journal, articles and books.